Clinical characterization and long‐term follow‐up of Schnitzler syndrome. (30th May 2016) - Gameiro, A.; Gouveia, M.; Pereira, M.; Tellechea, O.; Gonçalo, M.
Summary: Background: Schnitzler syndrome (SchS) is an acquired autoinflammatory disease characterized by chronic urticarial rash in association with monoclonal gammopathy. Patients may progress to lymphoproliferative disorders, but the associated factors and exact risk of progression are still not well defined. Aim: To characterize the clinical findings, laboratory abnormalities and histopathology of patients with SchS and their respective outcomes. Methods: We retrospectively reviewed the clinical files and the histological specimens of patients with SchS diagnosed from 1988 to 2015. Results: Nine patients (two women, seven men) were diagnosed with SchS. Mean age at diagnosis was 61.1 years (range 29–80), with a mean time to diagnosis of 3.7 years and a mean follow‐up period of 10.1 years (range 3–25). Four patients displayed an association of fever and arthralgia, and all nine patients consistently showed laboratory markers of inflammation. Serum values of the monoclonal component, IgMκ in eight patients and IgGλ in one patient, progressively increased over time. During follow‐up, carried out in association with the haematology department five patients progressed to lymphoproliferative disease, namely, lymphoplasmacytic lymphoma/Waldenström's macroglobulinaemia ( n = 4) and diffuse large B‐cell lymphoma ( n = 1). Conclusions: SchS is a rare chronic inflammatory disease with a substantial impact on quality of life. Our study highlights the importance of lifelong follow‐up for individuals with SchS, owing to the risk of progression to a lymphoproliferative disorder.